Effects of chitosan coating and different storage periods of broiler breeder eggs on growth performance and carcass characteristics - Koseman, Abdurrahman; Akdemir, Fatih; Seker, Ibrahim (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2020)
This study was carried out to determine the effects of coating with chitosan film and storing at different periods (7, 14, and 21 days) of broiler breeder eggs on growth performance and carcass characteristics of the chicks. The present study was arranged as three different storage periods (7, 14, and 21 days) and coating or not the eggs with chitosan film. In total, 1800 hatching fertilized eggs were used. These eggs were divided into six groups with 100 eggs in each and 600 eggs in each replication. A total of 751 chicks obtained from the hatching were used as material in this study. As a result, all chicks in the coated chitosan groups were alive during the 42-day growth period. The average hatching weight was determined as 42.7 +/- 0.1 g. The mean body weight (BW) of chicks on the 42nd day was determined as 2541.8 +/- 12.3 g in all groups. The effect of repetition on weekly BW and body weight gain (BWG) was found to be significant in the growth period. The differences between the groups for the BW were significant on day 1. While the weekly BWG varied, the growth performance was similar in the growth period in all groups. The differences between the groups in terms of slaughter weight and carcass characteristics were insignificant. It was determined that coating broiler eggs with chitosan and storing them in different periods does not have significantly negative effect on growth performance and carcass characteristics.
Keywords: broiler; carcass quality; egg; fattening